Effects of Wall Distensibility in Hemodynamic Simulations of an Arteriovenous Fistula - McGah, Patrick M. (2013)
Arteriovenous fistulae are created surgically to provide adequate access for dialysis patients suffering from end-stage renal disease. It has long been hypothesized that the rapid blood vessel remodeling occurring after fistula creation is in part a process to restore the mechanical stresses to some preferred level, i.e. mechanical homeostasis. The current study presents fluid-structure interaction (FSI) simulations of a patient-specific model of a mature arteriovenous fistula reconstructed from 3D ultrasound scans. The FSI results are compared with previously published data of the same model but with rigid walls. Ultrasound-derived wall motion measurements are also used to validate the FSI simulations of the wall motion. Very large time-averaged shear stresses, 10–15 Pa, are calculated at the fistula anastomosis in the FSI simulations, values which are much larger than what is typically thought to be the normal homeostatic shear stress in the peripheral vasculature. Although this result is systematically lower by as much as 50% compared to the analogous rigid-walled simulations, the inclusion of distensible vessel walls in hemodynamic simulations does not reduce the high anastomotic shear stresses to “normal” values. Therefore, rigid-walled analyses may be acceptable for identifying high shear regions of arteriovenous fistulae.